Validating a best practice : a tool for improvement and benchmarking - Van Nuland, Yves; Duffy, Grace L. (New York, NY : Routledge/Productivity Press, 2021)
Sharing Best Practices across industries and functions is an accepted approach to continuous improvement. The Benchmarking trend of the 1990s has evolved with the help of competitive analysis, performance excellence awards, and other corporate recognition programs into an ongoing documentation of what works. Bob Camp introduced benchmarking against a Best Practice based on his work at Xerox in the 1980s. Case studies abound documenting Best Practice functions and processes. Some case studies use the words Best Practice without evidence that the process, results, or methods are, indeed, superior. What is missing is a comprehensive model for assessing and writing a Best Practice that provides sufficient information to use as an effective benchmark. This book provides that comprehensive model. Today's consumers expect products and services to be of high quality, reliable, and user-friendly. This is the result of years of continuous improvement and innovation by producers. Although many organizations strive for excellent results, there is still room for improvement. Unfortunately, leaders don't always have methods and tools to measure or assess that degree of excellence. If leaders could use a tool to discover how good their approaches and methods are, and how excellent their achieved results are, they could plan further improvements. The goal is to achieve excellent results. The tool described in this book guides leaders to achieve that excellence.
4.3.8 Maturity of the Process -- 4.3.9 Key Performance Indicators (KPI) and Results -- 4.3.10 Distribution of the Results -- 4.3.11 Cause and Effect -- 4.3.12 Assessment of Enabler and Results -- 4.3.13 Limiting Conditions -- 4.3.14 Date and Revision Number -- 4.4 How Many Best Practices? -- Section II Use of The Best-Tool -- Chapter 5 Use of the Detailed BEST-Tool: Three Case Studies -- 5.1 Case Study 1 Organizational Culture Change at Lion Nathan (Australia) -- 5.1.1 Who is Lion Nathan? -- 5.1.2 Organization of Lion Nathan -- 5.1.3 History
"A Productivity Press book".
5.1.4 Three Pillars of Cultural Transformation Strategy
OCLC-licensed vendor bibliographic record.
Keywords: Benchmarking (Management); Total quality management; Performance standards -- Management; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science